Micro‐IDE: A tool platform for generating efficient deployment alternatives based on microservices. (25th April 2022) - Karabey Aksakallı, Işıl; Çelik, Turgay; Can, Ahmet Burak; Tekinerdoğan, Bedir
Abstract: Microservice architecture (MSA) is a paradigm to design and develop scalable distributed applications using loosely coupled, highly cohesive components that can be deployed independently. The applications that realize the MSA may contain thousands of services that together form the overall system. Microservices interact with each other by producing and consuming data. Deploying frequently communicating services to the same physical resource would reduce network utilization, which is vital for reducing costs and improving scalability. Since the physical resources have limited capacity, it is not always possible to deploy communicating services to the same resource. Therefore, automated efficient deployment alternatives need to be generated for MSA in the design phase. To address this problem, we proposed an algorithmic approach to generate efficient microservice deployment configurations to available cloud resources in our previous study. In this study, a tool (Micro‐IDE) has been proposed to realize and evaluate this approach. The Micro‐IDE tool has been validated using a case study inspired by the Spotify application.